(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
In the learning process, several gender-biased teaching materials, including textbooks in Indonesia, mostly prioritize men, meaning that gender roles are not balanced and there are gender stereotypes or biases. The research method used in this study is discourse analysis, to see the character of the contents of the Indonesian History textbook, both visible and hidden, with data validation obtained from literature studies and documentation studies. The implementation of this research is how gender is represented in the Indonesian History textbook published by the Ministry of Education and Culture. The research findings show that, in these two books, gender is mostly represented by using language that describes the concept of stereotypes, both male and female characters, although most of these gender stereotypes are not in accordance with their gender. The comparisons between the two textbooks are: In the Kemendikbud book, many characters are told with slightly superior gender traits, clear narratives, the author is more likely to express characters using language based on gender stereotypes, and seems to provide justification for the character’s attitudes that tend to be negative, by using language based on gender stereotypes. In other words, it is full of state goals.